Grounded Parallel RL, RC, and LC Immittance Simulators Using VDBAs and Passive Elements - Mongkolwai, Pratya; Moonmuang, Pitchayanin; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2022)
This communication suggests a grounded parallel RL, RC, and LC immittance simulator. In this circuit, two voltage differencing buffered amplifiers (VDBAs) with two passive components are proposed. The VDBA device's transconductance gain can be used to electronically adjust the realized equivalent resistance (Req), inductance (Leq), and capacitance (Ceq), which is conditional on the choice of the passive element. The effect of the VDBA's non-idealities on the realized simulator is studied in this research. The second order voltage mode bandpass filter is realized using the proposed active LC parallel simulator, which is simulated using the PSPICE simulation program to ensure that it operates as desired.
Keywords: electronically adjustable; immittance simulator; Voltage Differencing Buffered Amplifier (VDBA)